Chlorhexidine–alcohol versus iodine–alcohol for surgical site skin preparation in an elective arthroplasty (ACAISA) study: a cluster randomized controlled trial. (October 2019) - Peel, T.N.; Dowsey, M.M.; Buising, K.L.; Cheng, A.C.; Choong, P.F.M.
Abstract: Objectives: Surgical site skin preparation is an effective method to prevent wound complications. The optimal agent has not been established, and guidelines contain conflicting recommendations. Methods: The aim of alcoholic chlorhexidine or alcoholic iodine skin antisepsis (ACAISA) was to assess the efficacy of surgical site skin preparation with 0.5% chlorhexidine gluconate (w/v) in 70% ethanol (v/v) to 1% iodine (w/v) in 70% ethanol (v/v). This was a cluster randomized, controlled, single-centre, assessor-blinded, superiority trial in patients undergoing elective hip or knee arthroplasty. Each surgeon had a set operating day and the unit of randomization was the day of surgery. The primary outcome was superficial wound complication, defined as a composite endpoint of superficial incisional surgical site infection and/or clinically significant wound ooze in the 30 days following arthroplasty. The secondary outcome was any surgical site infection, including prosthetic joint infection. Outcome ascertainment was undertaken by an independent verification panel. The primary analysis was intention-to-treat, performed at the individual level. Taking into account the clustering effect, analysis of primary and secondary outcomes was undertaken at the level of the surgeon. Results: A total of 780 participants were included; 390 participants were allocated chlorhexidine–alcohol and 390 participants were allocated iodine–alcohol. There was no difference in superficial wound complications: 19 (4.9%) versus 15 (3.8%) respectively (OR 1.28; 95%CI 0.62, 2.63; p 0.50). There was an increased odds of surgical site infection in the chlorhexidine–alcohol group compared to iodine–alcohol: 12 (3.1%) versus four (1.0%) respectively (OR 3.06; 95%CI 1.26, 7.46; p 0.014). The odds of prosthetic joint infection were also increased in the chlorhexidine–alcohol arm compared with iodine–alcohol: seven (1.8%) versus two (0.5%) respectively (OR 3.55; 95%CI 1.20, 10.44; p 0.022). Conclusions: No difference was observed in the primary outcome of superficial wound complications when chlorhexidine–alcohol and iodine–alcohol were compared. However, on a secondary analysis, iodine–alcohol had greater efficacy than chlorhexidine–alcohol for preventing surgical site infection. Clinical Trial Registration: Australian New Zealand Clinical Trials Registry ACTRN12614000177651.